Trojan technology in the living room? Ethics of the “tipping point” between self-determination and heteronomy - Sonnauer, Franziska; Frewer, Andreas (Ethik in der Medizin, 2023)
Definition of the problem: Assistive technologies, including “smart” instruments and artificial intelligence (AI), are increasingly arriving in older adults’ living spaces. Various research has explored risks (“surveillance technology”) and potentials (“independent living”) to people’s self-determination from technology itself and from the increasing complexity of sociotechnical interactions. However, the point at which self-determination of the individual is overridden by external influences has not yet been sufficiently studied. This article aims to shed light on this point of transition and its implications. Arguments: The identification of this “tipping point” could contribute to analysis of familiar issues of conflict between the ethical principles of beneficence and respect for autonomy. When using technology in the living spaces of older adults, relationships, among other factors, may play a crucial role in older adult’s self-determination. We find the tipping point to occur subjectively and variably. To this end, the article combines theoretical ethical considerations with two examples from a qualitative study illustrating the perspective of older adults aged 65–85 years. Conclusion: The study of the tipping point underscores the importance of perceiving an older person’s perspective. Particularly at the tipping point, this might be the only way to effectively identify whether the individual concerned perceives their self-determination as externally overridden. In conceptualizing the tipping point itself as well as its variability, we might create the basis for a normative call to shift the tipping point to promote self-determination and prevent overriding the will of older adults. We highlight individual, relational, and societal implications of our findings.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Coercion; Gerotechnology; Home environment; Interpersonal relationships; Self-determination as a continuum